“Te’undur” Techniques for Sleep Disorders - Diana Pefbrianti; Devi Hairina Lestari; Diana Pefbrianti (International Journal Of Community Service, 2023)
Individuals who have hypertension often experience Complex issues such as sleep disturbances, pain, anxiety, and family support are low. So that individuals experience limitations in carrying out activities and are still dependent on other people around him. Non-pharmacological interventions with The retreat method can have a positive impact on the elderly who experience sleep disorders due to hypertension to maintain its life and always respond to the environment Surrounding. This community service is carried out in the village Tambak Baru ilir Martapura District, Banjar Regency City South Kalimantan. The measurement results obtained data that the elderly who experienced mild sleep disorders as much as 81.8% and those who experienced moderate sleep disorders as much as 18.2%. Te'undur is effective in overcoming sleep problems in the elderly caused by hypertension.Te'undur technique can provide relaxation / calm to respondents spiritually by saying istighfar or hamdalah accompanied by deep breathing techniques and loosening the muscles of the body.